Desmos Mathematics: Cultivating Critical Thinking Skills in Elementary Schools - Novitasari, Galuh; Novitasari, Meggy (Universitas Negeri Makassar, 2025)
This study aims to describe the use of desmos media in elementary mathematics learning and to analyze its role in fostering students’ critical thinking skills. The research employed a descriptive qualitative approach conducted at SDN 01 Jatikuwung through classroom observations, interviews, and document analysis. Data validity was ensured using source and method triangulation, while data were analyzed inductively through organizing, interpreting, and concluding processes. The findings show that the school supports the integration of digital media, and desmos math provides a positive impact on students’ learning. Students’ critical thinking skills increased significantly from an average of 29% before using Desmos to 85% after its implementation. The interactive visualizations helped students understand coordinate concepts, analyze information, and solve problems more systematically. Thus, Desmos Math is effective in enhancing conceptual understanding and strengthening students’ critical thinking abilities